Expression of GFP Gene in Gonads of Chicken Embryos by Transfecting Primordial Germ Cells in vitro or in vivo using the PiggyBac Transposon Vector System - Mitsuru Naito; Takashi Harumi; Takashi Kuwana (The Journal of Poultry Science, 2015)
In the present study, chicken primordial germ cells (PGCs) were transfected with GFP gene in vitro or in vivo using the piggyBac transposon vector system. PGCs cultured for 465 days were transfected in vitro, and GFP gene expression was observed in 25% of the treated PGCs after culturing for further 42 days. The cultured PGCs expressing GFP gene were transferred to recipient embryos and strong GFP gene expression was observed in the recipient gonads at day 18.5 of incubation. Circulating PGCs were transfected in vivo, and intense GFP gene expression was observed in the gonads of recipient embryos at day 18.5 of incubation. The procedure employed in the present study will contribute to successful gene transfer into chickens.